Cluster folding optical potential analysis for 6Li+28Si elastic scattering - Hamada, S.; Ibraheem, Awad A. (Revista Mexicana de Física, 2021)
Available experimental angular distribution data for 6Li+28Si elastic scattering in the energy range 16 – 318 MeV are re-analyzed phenomenologically on the basis of optical model using Woods-Saxon (WS) potentials for both real and imaginary parts, while the semi microscopic analysis was performed on the basis of cluster folding potential. Cluster folding potential was generated based on the appreciable cluster structure and breakup of 6Li into a deuteron orbiting a core of α-particle. Although several data sets in a wide range of energies are subjected to investigation, the theoretical calculations using the different concerned potentials are fairly reproduced the experimental data in the whole energy range. The extracted real and imaginary volume integrals and reaction cross sections values are compared to the previously reported ones and they found to be in a good agreement